Microstructure of Snow and Its Link to Trace Elements and Isotopic Composition at Kohnen Station, Dronning Maud Land, Antarctica - Moser, Dorothea Elisabeth; Hörhold, Maria; Kipfstuhl, Sepp; Freitag, Johannes (Frontiers in Earth Science, 2020)
Understanding the deposition history and signal formation in ice cores from polar ice sheets is fundamental for the interpretation of paleoclimate reconstruction based on climate proxies. Polar surface snow responds to environmental changes on a seasonal time scale by snow metamorphism, displayed in the snow microstructure and archived in the snowpack. However, the seasonality of snow metamorphism and accumulation rate is poorly constrained for low-accumulation regions, such as the East Antarctic Plateau. Here, we apply core-scale microfocus X-ray computer tomography to continuously measure snow microstructure of a 3-m deep snow core from Kohnen Station, Antarctica. We compare the derived microstructural properties to discretely measured trace components and stable water isotopes, commonly used as climate proxies. Temperature and snow height data from an automatic weather station are used for further constraints. Dating of the snow profile by combining non-sea-salt sulfate and density crusts reveals a seasonal pattern in the geometrical anisotropy. Considering seasonally varying temperature-gradient metamorphism in the surface snow and the timing of the anisotropy pattern observed in the snow profile, we propose the anisotropy to display the deposition history of the site. An annually varying fraction of deposition during summer months, ranging from no or negative deposition to large deposition events, leads to the observed microstructure and affects trace components as well as stable water isotopes.